ETIKA MENYAMPAIKAN KRITIK DALAM ISLAM: Analisis Penafsiran Ibnu Katsir dan Hamka tentang Qaulan Layyina dalam Surat Taha Ayat 44 - Roni, Rodiana (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2021)
In this study the author wants to reveal these differences by collecting two books of tafsir namely Tafsir al-Qur`an al-Adzim and Tafsir al-Azhar as well as books related to the research, which method is often called library research. Then the two commentaries are compared and analyzed in detail with books relevant to this research. This research produces some differences and similarities of the two commentaries. With the means or media to convey a criticism or suggestion at this time such as through social media or print media must use wise, polite and gentle language with the aim that the criticism can be accepted and used as constructive criticism. Keywords : Qaulan Layyina, Ethics, Criticism, Leader.